The strength training anatomy workout II - Delavier, Frédéric (Human Kinetics, 2010)
Go inside exercises, stretches, and workouts to see how muscles interact with surrounding joints and skeletal structures, and how variations, progressions, and sequencing can affect muscle recruitment, the underlying structures, and ultimately the results.--